A hole transport layer with gradient optical band gap and preparation method thereof and perovskite solar cell
By regulating the SnOx film to be P-type and forming a hole transport layer with gradient optical band gap, the problem of low long-term operation stability of perovskite solar cells is solved, and the photoelectric conversion efficiency and stability are improved.
Patent Information
- Application Number
- CN202411035363.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-31
AI Technical Summary
The long-term operation stability of existing perovskite solar cells is low, especially because the material corresponding to Ni≥3+ has a high reactivity, which leads to a redox reaction with the perovskite materials, reducing its stability.
By regulating the SnOx film to be P-type and forming a hole transport layer with a gradient optical band gap, optical loss problems caused by relatively narrow band gaps due to excessive content of P-type SnO are avoided.
On the premise of ensuring transmission performance, the photo loss caused by excessive content of incompletely oxidized SnOx materials is reduced, and the photoelectric conversion efficiency and long-term operation stability of perovskite solar cells are improved.
Smart Images

Figure CN118574434B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cell materials, and in particular relates to a hole transport layer with a gradient optical band gap, a preparation method thereof, and a perovskite solar cell. Background Art
[0002] Perovskite photoelectric materials have attracted extensive attention from academia and industry since their emergence in 2009 due to their advantages of high extinction coefficient, long carrier lifetime, high photoelectric conversion efficiency, and diverse and simple preparation routes. In recent years, the highest efficiency of a single small-area perovskite cell has reached 26.1%, and the efficiency and large-area expansion of perovskite solar cells have basically broken through the bottleneck, with great application prospects.
[0003] However, it is reported that the operating stability of perovskite solar cells is still at thousands of hours, so in order to further industrialize, it is urgent to solve the problem of improving the long-term operating stability of perovskite solar cells. The factors that affect the long-term operating stability of perovskite solar cells mainly include the following: the composition of the perovskite light-absorbing layer, the overall device structure, the material composition of each functional layer, and the external packaging components.
[0004] The hole transport layer disclosed in the prior art is generally prepared by a solution method using an organic polymer or a single-molecule self-assembled organic layer. However, the above-mentioned materials are expensive and difficult to expand over a large area. At the same time, the long-term operating stability of the organic components is still insufficient. Therefore, inorganic hole transport layers with higher stability have received widespread attention.
[0005] Currently, the materials of commercial inorganic hole transport layers mainly include NiO x , CuSCN, etc. Since pure NiO material is not conductive, as the proportion of Ni≥3+ increases, the conductivity of the corresponding material also increases. However, the reaction activity of the material corresponding to Ni≥3+ is higher, so it can undergo redox reaction with the perovskite material, ultimately reducing its long-term operation stability.
[0006] Therefore, in the art, there is an urgent need to develop an efficient inorganic hole transport layer to solve the above problems. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide a hole transport layer with a gradient optical band gap, a preparation method thereof and a perovskite solar cell. x The film is P-type, which enables it to be used as a hole transport layer for perovskite solar cells, and further forms a hole transport layer with a gradient optical band gap, thereby avoiding the problem of optical loss caused by a relatively narrow band gap due to excessive content of P-type SnO.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a hole transport layer having a gradient optical band gap, wherein the hole transport layer having a gradient optical band gap comprises a first hole transport layer and a second hole transport layer which are stacked;
[0010] The material of the first hole transport layer includes a first p-type SnO x The material of the second hole transport layer includes a second p-type SnO x , where 1≤x<2;
[0011] The optical band gap of the first hole transport layer is lower than the optical band gap of the second hole transport layer.
[0012] It should be noted that the value range of x is 1≤x<2, for example, it can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, etc.
[0013] On the one hand, the present invention regulates SnO x The incomplete oxidation process of the material, and further optimize the value range of x, so that SnO x The material is p-type, so it can act as a hole transport layer; on the other hand, the optical band gap of pure SnO material is 2.6-3.0eV, so compared with SnO2 material with a wider optical band gap (3.6-4.0eV), its absorption of light is stronger and the light transmittance is lower. Therefore, the present invention adjusts the optical band gap of the first hole transport layer to be lower than the optical band gap of the second hole transport layer, so as to form a hole transport layer with a gradient optical band gap, which further reduces the optical band gap caused by incomplete oxidation of SnO while ensuring the transmission performance. x Excessive material content causes the negative impact of light loss, which ultimately improves the photoelectric conversion efficiency and long-term operation stability of perovskite solar cells.
[0014] Preferably, the first p-type SnO x The value range of x is 10 / 9≤x≤10 / 7, for example, it can be 1.11, 1.2, 1.22, 1.25, 1.28, 1.3, 1.32, 1.35, 1.38, 1.4, 1.42, etc.
[0015] In the present invention, by regulating the first p-type SnO x The value range of x in the above formula is to produce more incompletely oxidized Sn. 2+ , x values that are too large tend to generate more Sn 4+ , the film gradually transforms to N-type with a wider band gap.
[0016] Preferably, the second p-type SnO x The value range of x is 10 / 7<x≤5 / 3, for example, it can be 1.45, 1.48, 1.5, 1.52, 1.55, 1.58, 1.6, 1.62, 1.65, etc.
[0017] In the present invention, by regulating the second p-type SnO x The value range of x in the film is such that 4+ If the value of x is too small, more Sn will be generated. 2+ , and the formed film gradually transforms to p-type, causing increased light loss.
[0018] Preferably, the optical band gap of the first hole transport layer is 2.8-3.2 eV, for example, 2.8 eV, 2.9 eV, 3.0 eV, 3.1 eV, 3.2 eV, etc.
[0019] Preferably, the optical band gap of the second hole transport layer is greater than 3.2 eV and not higher than 3.4 eV, for example, it may be 3.25 eV, 3.28 eV, 3.3 eV, 3.32 eV, 3.35 eV, 3.38 eV, 3.4 eV, etc.
[0020] Preferably, the thickness of the first hole transport layer is 3-8 nm, for example, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, etc.
[0021] Preferably, the thickness of the second hole transport layer is 3-8 nm, for example, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, etc.
[0022] In the present invention, by adjusting the thickness of the first hole transport layer and the second hole transport layer, the formed film is formed under the premise of being p-type, and the internal Sn 4+ increases, and the band gap widens, which further reduces the light absorption.
[0023] In a second aspect, the present invention provides a method for preparing a hole transport layer having a gradient optical band gap according to the first aspect, the method comprising the following steps:
[0024] The first p-type SnO x The material is prepared to obtain a first hole transport layer, wherein 1≤x<2;
[0025] The second p-type SnO x The material is prepared to obtain a second hole transport layer, wherein 1≤x<2;
[0026] The first hole transport layer and the second hole transport layer are stacked to obtain the hole transport layer with a gradient optical band gap, wherein the optical band gap of the first hole transport layer is lower than the optical band gap of the second hole transport layer.
[0027] Preferably, the first p-type SnO x Methods for preparing materials to obtain the first hole transport layer include atomic layer deposition, plating and coating, preferably atomic layer deposition.
[0028] Preferably, the process of preparing the first hole transport layer by atomic layer deposition includes: first performing a 0.05-5s tin source pulse; then purging with nitrogen for 10-30s; secondly performing a 0.05-5s oxygen source pulse; and finally purging with nitrogen for 10-30s. The number of atomic layer deposition cycles is 60 and the operating temperature is 80-90°C.
[0029] In the present invention, during the atomic layer deposition method, tetrakis(dimethylamino)tin is used as a tin source and water is used as an oxygen source. Tetrakis(dimethylamino)tin and water are pulsed alternately into a vacuum reaction chamber and several atomic layer deposition cycles are performed.
[0030] Preferably, the second p-type SnO x Methods for preparing materials to obtain the second hole transport layer include atomic layer deposition, plating and coating, preferably atomic layer deposition.
[0031] Preferably, the process of preparing the second hole transport layer by atomic layer deposition includes: first performing a 0.05-5s tin source pulse; then purging with nitrogen for 10-30s; secondly performing a 0.05-5s oxygen source pulse; and finally purging with nitrogen for 10-30s. The number of atomic layer deposition cycles is 60 and the operating temperature is 90-105°C.
[0032] In the present invention, during the atomic layer deposition method, tetrakis(dimethylamino)tin is used as a tin source and water is used as an oxygen source. Tetrakis(dimethylamino)tin and water are pulsed alternately into a vacuum reaction chamber and several atomic layer deposition cycles are performed.
[0033] In a third aspect, the present invention provides a perovskite solar cell, comprising a substrate layer, a first carrier transport layer, a perovskite light absorbing layer, a second carrier transport layer and a metal electrode layer stacked in sequence, wherein the first carrier transport layer and the second carrier transport layer are each independently selected from an electron transport layer or a hole transport layer, and the hole transport layer comprises a hole transport layer with a gradient optical band gap according to the first aspect.
[0034] Preferably, when the first carrier transport layer is a hole transport layer, the first hole transport layer is arranged on the surface of the base layer, and the second hole transport layer is arranged on the surface of the first hole transport layer away from the base layer.
[0035] Preferably, when the second carrier transport layer is a hole transport layer, the first hole transport layer is arranged on the surface of the metal electrode layer, and the second hole transport layer is arranged on the surface of the first hole transport layer away from the metal electrode layer.
[0036] Preferably, the material of the electron transport layer includes C 60 Electron transport layer and tin dioxide electron transport layer.
[0037] Preferably, the C 60 The thickness of the electron transport layer is 5-20 nm, for example, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, etc.
[0038] In the present invention, the C 60 The electron transport layer can be prepared by vacuum evaporation.
[0039] Preferably, the thickness of the tin dioxide electron transport layer is 10-20 nm, for example, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, etc.
[0040] In the present invention, the tin dioxide electron transport layer can be prepared exemplarily by atomic layer deposition, and the specific parameters include: using tetrakis(dimethylamino)tin as a tin source and water as an oxygen source, alternately pulse tetrakis(dimethylamino)tin and water into a vacuum reaction chamber, and performing several atomic layer deposition cycles, wherein the atomic layer deposition cycle includes: first performing a 0.1s tin source pulse; then purging with nitrogen for 10s; secondly performing a 0.08s oxygen source pulse; and finally purging with nitrogen for 10s. The number of atomic layer deposition cycles is 150, and the operating temperature is 105°C.
[0041] In the present invention, the material of the perovskite light absorbing layer exemplarily includes FA 0.8 Cs 0.25 Pb(I 0.8 Br 0.2 )3.
[0042] In the present invention, the perovskite solar cell device is not limited to perovskite tandem cells and single-cell cells, and the tandem cells include but are not limited to all-perovskite tandem cells, for example, perovskite-crystalline silicon tandem cells, perovskite-thin film cells (CIGS) tandems, cadmium telluride (CdTe) / perovskite tandem cells, etc.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] The present invention provides a hole transport layer with a gradient optical band gap. On the one hand, the present invention adjusts SnO x The incomplete oxidation process of the material, and further optimize the value range of x, so that SnO x The material is p-type, so it can act as a hole transport layer; on the other hand, the optical band gap of pure SnO material is 2.6-3.0eV, so compared with SnO2 material with a wider optical band gap (3.6-4.0eV), its absorption of light is stronger and the light transmittance is lower. Therefore, the present invention adjusts the optical band gap of the first hole transport layer to be lower than the optical band gap of the second hole transport layer, so as to form a hole transport layer with a gradient optical band gap, which further reduces the optical band gap caused by incomplete oxidation of SnO while ensuring the transmission performance. x Excessive material content causes the negative impact of light loss, which ultimately improves the photoelectric conversion efficiency and long-term operation stability of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 The p-type SnO provided by the present invention x Schematic diagram of the incomplete oxidation mechanism of the material;
[0046] Figure 2 This is a schematic structural diagram of the perovskite solar cell provided by the present invention. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0048] Example 1
[0049] This embodiment provides a hole transport layer with a gradient optical band gap, such as Figure 1-Figure 2 As shown, the hole transport layer with a gradient optical band gap includes a first hole transport layer and a second hole transport layer stacked in layers; the material of the first hole transport layer includes a first p-type SnO x , the optical band gap is 2.9eV, and the thickness is 5nm; the material of the second hole transport layer includes a second p-type SnO x, the optical band gap is 3.25eV and the thickness is 5nm.
[0050] This embodiment also provides a method for preparing the hole transport layer having a gradient optical band gap, which comprises the following steps:
[0051] The preparation is carried out by atomic layer deposition, wherein the tin source is tetrakis(dimethylamino)tin, and water is used as the oxygen source. The process of atomic layer deposition in the first hole transport layer includes: alternately pulse tetrakis(dimethylamino)tin and water into a vacuum reaction chamber, and perform several atomic layer deposition cycles, wherein the atomic layer deposition cycle includes: firstly perform a 1s tin source pulse; then purge with nitrogen for 10s; secondly perform a 0.08s oxygen source pulse; and finally purge with nitrogen for 10s. The number of atomic layer deposition cycles is 60 times, and the operating temperature is 85°C. The process of atomic layer deposition in the second hole transport layer includes: alternately pulse tetrakis(dimethylamino)tin and water into a vacuum reaction chamber, and perform several atomic layer deposition cycles, wherein the atomic layer deposition cycle includes: firstly perform a 1s tin source pulse; then purge with nitrogen for 10s; secondly perform a 0.08s oxygen source pulse; and finally purge with nitrogen for 10s. The number of atomic layer deposition cycles is 60 times, and the operating temperature is 105°C.
[0052] This embodiment also provides an inverse perovskite solar cell and a preparation method thereof, as shown below:
[0053] (1) FTO conductive glass with a square resistance of 8Ω and a transmittance of 88% was used, which was cleaned in a standard manner and then treated with UV-ozone for 20 minutes for use;
[0054] (2) using the above-mentioned hole transport layer with gradient optical band gap;
[0055] (3) The material of the perovskite light-absorbing layer is FA 0.8 Cs 0.25 Pb(I 0.8 Br 0.2 )3, prepare it with a mixed solvent (the volume ratio of DMF to DMSO is 4:1) to form a perovskite solution, first spin-coat it at a speed of 1000r for 10s, and then spin-coat it at a speed of 4500r for 35s, and add the anti-solvent ethyl acetate in the remaining 17s of the high-speed stage. After the spin coating, anneal it at 100°C for 20min to obtain the perovskite light-absorbing layer;
[0056] (4) Evaporation C 60 Layer: C was prepared by high vacuum evaporation method 60 Electron transport layer, thickness 15nm, evaporation rate 0.01nm / s;
[0057] Atomic layer deposition of N-type SnO2: wherein the tin source is tetrakis(dimethylamino)tin, and water is used as the oxygen source. The process of atomic layer deposition includes: alternately pulse tetrakis(dimethylamino)tin and water into a vacuum reaction chamber, and perform several atomic layer deposition cycles, wherein the atomic layer deposition cycle includes: firstly perform a 0.1s tin source pulse; then perform a 10s nitrogen purge; secondly perform a 0.08s oxygen source pulse; and finally perform a 10s nitrogen purge. The number of atomic layer deposition cycles is 150, and the operating temperature is 105°C.
[0058] (5) Metal electrode: The metal electrode was prepared by high vacuum thermal evaporation method with a thickness of 120 nm and an evaporation rate of 0.1 nm / s.
[0059] Example 2
[0060] The difference between this embodiment and the first embodiment is that the working temperature during the atomic layer deposition of the first hole transport layer is adjusted to 150° C., and the rest is the same as the first embodiment.
[0061] Example 3
[0062] The difference between this embodiment and the first embodiment is that the working temperature during the atomic layer deposition of the second hole transport layer is adjusted to 150° C., and the rest is the same as the first embodiment.
[0063] Example 4
[0064] The difference between this embodiment and embodiment 1 is that the pulse deposition time of the tin source during the atomic layer deposition of the first hole transport layer and the second hole transport layer is adjusted to 0.1 s, and the rest is the same as embodiment 1.
[0065] Example 5
[0066] The difference between this embodiment and embodiment 1 is that the pulse deposition time of the tin source during the atomic layer deposition of the first hole transport layer and the second hole transport layer is adjusted to 0.1 s, and the working temperature is adjusted to 150° C., and the rest is the same as embodiment 1.
[0067] Example 6
[0068] The difference between this embodiment and embodiment 1 is that the pulse deposition time of the oxygen source during the atomic layer deposition of the first hole transport layer and the second hole transport layer is adjusted to 1 s, and the rest is the same as embodiment 1.
[0069] Example 7
[0070] The difference between this embodiment and embodiment 1 is that the thickness of the first hole transport layer is 15 nm, and the rest is the same as embodiment 1.
[0071] Example 8
[0072] The difference between this embodiment and the first embodiment is that the thickness of the second hole transport layer is 15 nm, and the rest is the same as the first embodiment.
[0073] Comparative Example 1
[0074] The difference between this comparative example and Example 1 is that the hole transport layer with gradient optical band gap is replaced by NiO x The hole transport layer is prepared as follows:
[0075] Preparation of NiO by magnetron sputtering x Hole transport layer, NiO x The size of the ceramic target is 3 inches, the RF power is 100W, the target spacing is 15cm, the working pressure in pure argon atmosphere is 0.3Pa, and the NiO x The thickness of the hole transport layer is 14 nm, and the rest is the same as in Example 1.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 1 is that the hole transport layer with a gradient optical band gap is replaced by a self-assembled monolayer SAM MeO-2PACz hole transport layer, and the preparation method is as follows:
[0078] SAM MeO-2PAC was prepared into a methanol solution with a concentration of 0.5 mg / mL, and was spin-coated at a speed of 3000 r for 30 s using a spin coater, and then annealed at 100° C. for 15 min. The other preparation methods were the same as those in Example 1.
[0079] Comparative Example 3
[0080] The difference between this comparative example and Example 1 is that only the first hole transport layer is provided, the number of cycles of atomic layer deposition in the first hole transport layer is 120 times, and the rest is the same as Example 1.
[0081] Comparative Example 4
[0082] The difference between this comparative example and Example 1 is that only the second hole transport layer is provided, the number of cycles of atomic layer deposition in the second hole transport layer is 120 times, and the rest is the same as Example 1.
[0083] Test conditions
[0084] The perovskite solar cells provided by Examples 1 to 8 and Comparative Examples 1 to 4 were tested, and the testing method was as follows:
[0085] The perovskite solar cells prepared in the above embodiments and comparative examples were subjected to photoelectric conversion efficiency tests and 1000h stability tracking, with 12 cells in each group and 4 sub-cells in each cell, and the efficiency results were the statistical averages of 48 groups of data. The 1000h stability tracking test was performed to eliminate the influence of the packaging process. All cells were not packaged and placed in an inert atmosphere glove box. They were taken out for efficiency tracking at each test, and the tracking time exceeded 1000h, and the percentage of the remaining initial efficiency was obtained.
[0086] The test results are shown in Table 1:
[0087] Table 1
[0088]
[0089] From Table 1, we can see the following conclusions:
[0090] As shown in Table 1, the statistical parameters of the photoelectric performance indicators of the prepared perovskite solar tandem cell device are shown in Table 1. By comparing Example 1 with Example 2-Example 3, it can be seen that Example 2-Example 3 shows that after being treated at a high temperature of 150°C, the p-type SnO x It will be completely oxidized into SnO2, that is, an n-type thin film is prepared, but it does not have the ability to transport holes. Therefore, the photoelectric performance of the materials prepared in Example 2-Example 3 when used as a hole transport layer is poor, that is, the photoelectric efficiency of the perovskite solar tandem cell device is not higher than 10%.
[0091] Comparison between Example 1 and Example 4-Example 5 shows that Example 4 can adjust the content of the tin source by changing the pulse deposition time of the tin source. The pulse deposition time of the tin source is adjusted to 0.1s so that SnO x The proportion of SnO2 in the film increases, and finally SnO x The film gradually changes from p-type to n-type, which hinders the hole transport performance of the material, and the overall performance of the assembled perovskite solar tandem cell device also decreases. Further, in Example 5, the prepared SnO x The film is almost entirely composed of n-type SnO2 material, so the final hole transport layer has no hole transport performance at all and the photoelectric conversion efficiency is the lowest, which is only 4.5%.
[0092] Compared with Example 1, Example 6 adjusts the pulse deposition time of the oxygen source (water) to the standard time of 1 s, and the tin source is transformed from a highly incompletely oxidized state to a fully oxidized state, that is, more Sn 2+ Oxidized to Sn 4+ , making some p-type SnO xIt becomes n-type, at which time the ratio between SnO2 and SnO is close, so SnO x The hole transmission capacity will decrease accordingly, and the overall performance of the assembled perovskite solar tandem cell device will also decrease.
[0093] Comparison between Examples 1, 2 to 6 shows that due to the p-type SnO x Gradually or completely converted to n-type SnO x , resulting in an incomplete structure of the perovskite solar tandem cell device, making its photoelectric performance poor, and the corresponding stability will also deteriorate.
[0094] From the comparison between Example 1 and Example 7-Example 8, it can be seen that the excessive thickness of the first hole transport layer or the first hole transport layer mainly affects the light absorption efficiency of the device and the filling factor of the device, making the filling factor and the current density lower, and the corresponding carrier extraction ability worse, so the photoelectric conversion efficiency of the perovskite solar tandem cell device is poor.
[0095] Comparative Example 1: NiO prepared by magnetron sputtering x The structure of contains Ni≥3+, so it is reactive with the perovskite material, so the perovskite solar tandem cell device has low opening voltage loss and filling factor, and its long-term operation stability is poor. Although the hole transport material used in comparative example 2 has a high photoelectric conversion efficiency, it is an organic component and is sensitive to water, oxygen and ambient temperature. Therefore, the efficiency of the perovskite solar tandem cell device remains only 68% after long-term operation for 1000h.
[0096] Comparative Example 3 only sets a single high non-completely oxidized p-type SnO x layer, due to the high incomplete oxidation of SnO x The band gap is relatively narrow, and there is a certain absorption of light, so the current density of the perovskite solar tandem cell device becomes low. x Although the band gap is wide and has good light transmission efficiency, the p-type SnO x Sn 4+ The proportion of is high, which makes the hole transport layer's ability to transport holes worse. Therefore, the open circuit voltage and fill factor of the perovskite solar tandem cell device are significantly reduced, and only 16% of the photoelectric conversion efficiency is achieved.
[0097] In summary, the present invention provides a p-type SnO with a gradient optical band gap. x Hole transport layer and preparation method thereof, and further reduce the SnO2 due to incomplete oxidation by regulating its incomplete oxidation process while ensuring the transport performancex Excessive material content causes the negative impact of light loss, which ultimately improves the photoelectric conversion efficiency and long-term operation stability of perovskite solar cells.
[0098] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A hole transport layer with a gradient optical band gap for a perovskite cell, characterized in that: The hole transport layer with a gradient optical band gap comprises a first hole transport layer and a second hole transport layer which are stacked; The material of the first hole transport layer includes a first p-type SnO x The material of the second hole transport layer includes a second p-type SnO x , where 1≤x<2; The optical band gap of the first hole transport layer is 2.8-3.2 eV; The optical band gap of the first hole transport layer is lower than the optical band gap of the second hole transport layer; The first p-type SnO x The first hole transport layer and the second p-type SnO x The method for preparing the material to obtain the second hole transport layer is atomic layer deposition; The process of preparing the first hole transport layer by atomic layer deposition includes: firstly, performing a 1-5s tin source pulse; then, purging with nitrogen for 10-30s; secondly, performing a 0.05-0.08s oxygen source pulse; and finally, purging with nitrogen for 10-30s. The number of atomic layer deposition cycles is 60 times, and the working temperature is 80-90°C. The process of preparing the second hole transport layer by atomic layer deposition includes: firstly performing a 1-5s tin source pulse; then purging with nitrogen for 10-30s; secondly performing a 0.05-0.08s oxygen source pulse; and finally purging with nitrogen for 10-30s. The number of atomic layer deposition cycles is 60 times, and the working temperature is 90-105°C.
2. The hole transport layer with a gradient optical band gap according to claim 1, characterized in that: The first p-type SnO x The value range of x is 10 / 9≤x≤10 / 7.
3. The hole transport layer with gradient optical band gap according to claim 1, characterized in that: The second p-type SnO x The value range of x is 10 / 7<x≤5 / 3.
4. The hole transport layer with a gradient optical band gap according to claim 1, characterized in that: The optical band gap of the second hole transport layer is greater than 3.2 eV and not higher than 3.4 eV.
5. The hole transport layer with gradient optical band gap according to claim 1, characterized in that: The thickness of the first hole transport layer is 3-8 nm.
6. The hole transport layer with gradient optical band gap according to claim 1, characterized in that: The thickness of the second hole transport layer is 3-8 nm.
7. A method for preparing a hole transport layer having a gradient optical band gap according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: The first p-type SnO x The material is prepared to obtain a first hole transport layer, wherein 1≤x<2; The second p-type SnO x The material is prepared to obtain a second hole transport layer, wherein 1≤x<2; The first hole transport layer and the second hole transport layer are stacked to obtain the hole transport layer with a gradient optical band gap, wherein the optical band gap of the first hole transport layer is lower than the optical band gap of the second hole transport layer; The method of preparing the first hole transport layer from the first p-type SnOx material and preparing the second hole transport layer from the second p-type SnOx material is an atomic layer deposition method; The process of preparing the first hole transport layer by atomic layer deposition includes: firstly, performing a 1-5s tin source pulse; then, purging with nitrogen for 10-30s; secondly, performing a 0.05-0.08s oxygen source pulse; and finally, purging with nitrogen for 10-30s. The number of atomic layer deposition cycles is 60 times, and the working temperature is 80-90°C. The process of preparing the second hole transport layer by atomic layer deposition includes: firstly performing a 1-5s tin source pulse; then purging with nitrogen for 10-30s; secondly performing a 0.05-0.08s oxygen source pulse; and finally purging with nitrogen for 10-30s. The number of atomic layer deposition cycles is 60 times, and the working temperature is 90-105°C.
8. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a substrate layer, a first carrier transport layer, a perovskite light absorbing layer, a second carrier transport layer and a metal electrode layer which are stacked in sequence, wherein the first carrier transport layer and the second carrier transport layer are each independently selected from an electron transport layer or a hole transport layer, and the hole transport layer comprises a hole transport layer having a gradient optical band gap according to any one of claims 1 to 6.
9. The perovskite solar cell according to claim 8, characterized in that: When the first carrier transport layer is a hole transport layer, the first hole transport layer is arranged on the surface of the base layer, and the second hole transport layer is arranged on the surface of the first hole transport layer away from the base layer.
10. The perovskite solar cell according to claim 8, characterized in that: When the second carrier transport layer is a hole transport layer, the first hole transport layer is arranged on the surface of the metal electrode layer, and the second hole transport layer is arranged on the surface of the first hole transport layer away from the metal electrode layer.
11. The perovskite solar cell according to claim 8, characterized in that: The material of the electron transport layer includes C 60 Electron transport layer and tin dioxide electron transport layer.
12. The perovskite solar cell according to claim 11, characterized in that: The C 60 The thickness of the electron transport layer is 5-20 nm.
13. The perovskite solar cell according to claim 11, characterized in that: The thickness of the tin dioxide electron transport layer is 10-20 nm.
Citation Information
Patent Citations
NiOx hole transport layer in solar cell and preparation method and application thereof
CN116314439A